REPRESENTASI PEREMPUAN DALAM LAGU RAP PRANCIS - Fredyansah, Muhamad Arif; Wahyuddin, Wahyuddin; Bandu, Irianty (SENTRI: Jurnal Riset Ilmiah, 2023)
This research aims to reveal the strategies used to represent women in French rap songs and identify the various identities of women depicted in French rap songs. This research utilizes Sara Mills' Critical Discourse Analysis theory and Halliday's Systemic Functional Linguistics approach on Transitivity. The data were then analyzed using Sara Mills' Critical Discourse Analysis theory, focusing on the subject and object positions. These clauses were classified based on transitivity elements, including participants, processes, and circumstances. The results show differences in the representation of women carried out by male and female rappers. In songs performed by male rappers, women are represented as object. Women are portrayed as materialistic, seductive, traditional, and passive. Based on the transitivity analysis, which indicates that the dominant processes are Material, Mental, and Relational processes. On the other hand, in rap songs performed by female rappers, women are represented as subject, capable of presenting themselves and offering representations that tend to empower women. This representation manifests as strong, confident, independent, and competitive women. This is also evident from the transitivity analysis, which indicates that the dominant process is the Material process